Influence of refractive index profile of ring-core fibres for space division multiplexing systems - Jin, X; Gomez, A; O'Brien, D; Payne, F (IEEE, 2014)
Modal properties of step/graded-index ring-core fibres (SI/GI-RCFs) are investigated and compared for application in space-division multiplexing systems.